Occupational health psychology and management: psychosocial risk management in the oil and gas industry - Bergh, Linn Iren Vestly Bergh (2017)
International bodies and networks within occupational health and occupational health psychology have over the last years highlighted a pressing need to understand how research and best practices can be translated into sustainable business practice.